Body weight estimation from body measures in Cornigliese sheep breed. Issue 1 (14th December 2020) - Sabbioni, Alberto; Beretti, Valentino; Superchi, Paola; Ablondi, Michela
Abstract: The aim of this research is to propose equations to estimate body weight (BW) from body measures (BMs) in the Cornigliese sheep, an endangered breed reared in Italy for meat purpose. BW and BMs were submitted to correlation and multiple regression analyses. Two datasets were used: (i) 303 animals (178 females, 125 males, BW 4.00–117.80 kg), on which BW, height at withers (HW), chest circumference (ChC) and body length (BL) were measured; (ii) 156 animals (109 females, 47 males, BW 5.15–117.80 kg) out of 303 on which croup height (HCr), chest width (ChW), chest depth (ChD) and croup width (CrW) were also considered. On each dataset, two regression models were applied, one containing all variables (models 1 and 3, respectively, for datasets 1 and 2) and the other one comprising groups of variables, selected by means of the stepwise procedure (models 2 and 4, respectively, for datasets 1 and 2). BW resulted correlated with all BMs (from 0.852 for ChW to 0.950 for ChC; p < .001). Models 1 and 3 fitted the data better than models 2 and 4, both for all animals and for females and males separately. We concluded that BW could be predicted from BMs also in Cornigliese sheep breed. The best fits were obtained when the highest number of measures was included in the model (models 1 and 3). Nevertheless, models 2 and 4 could be used more easily in extensive sheep breeding than models 1 and 3, since they require less parameters. Highlights: The estimation of body weight is important in a meat type sheep breed for choosing the optimal slaughter time. A reduction of work for farmer is positive, mainly in field conditions of extensive rearing, where scales are not easily available. Body weight could be predicted from body measures in Cornigliese sheep breed with good precision and accuracy.